First report of fusF gene in Staphylococcus kloosii from virgin tropical soil: expanding the ecological reservoirs of fusidic acid resistance - Ruzaini Abdullah, Muhammad Haziq; Mohd Zainudin, Mohd Huzairi; A. Aljaberi, Musheer; Abdul Mutalib, Noor Azira; Neoh, Hui Min; Awang Hamat, Rukman (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Fusidic acid resistance in Staphylococcus spp. has historically been confined to Staphylococcus ureilyticus, with limited data on its environmental distribution. This study presents the first detection of the fusidic acid resistance gene fusF in Staphylococcus kloosii recovered from virgin soil at Kampung Batu 16, Dusun Tua, Hulu Langat, Malaysia. A total of ten Staphylococcus isolates were identified using the VITEK®2 system with high confidence (97–99%), comprising seven S. kloosii and three S. ureilyticus. Sequencing of representative isolates further corroborated the species identification. All isolates displayed phenotypic resistance to fusidic acid, while all S. ureilyticus (3/3) exhibited multi-drug resistant (MDR) traits and S. kloosii (7/7) exhibited non-MDR traits. PCR and sequencing confirmed the presence of fusF gene in S. ureilyticus (3/3) and S. kloosii (3/7). In addition, fusB and fusC genes were not detected in both species. The phylogenetic analysis (Maximum Likelihood, Tamura–Nei model) revealed high sequence conservation and clustering between fusF-positive S. kloosii and S. ureilyticus soil isolates, suggesting recent horizontal gene transfer between these two related species. The first detection of fusF gene in S. kloosii from virgin soil signifies the expansion of the ecological and host range beyond S. ureilyticus, establishes virgin soil as a potential antimicrobial resistance (AMR) reservoir, and underscores the One Health risks of resistance dissemination from environmental staphylococci. This baseline study highlights the importance of early AMR surveillance in tropical environments prior to agricultural development.